Results of Retrograde K-Wire Fixation in Diaphyseal Fractures of Forearm in Children - Shrestha, Dinesh Kumar; Karki, Prateek; Lakhanpal, V. P.; Mishra, S. M. (Journal of Nepalgunj Medical College, 2017)
Background: Diaphyseal fractures of forearm is the third most common fracture in children. Majority of these fractures can be treated with close reduction and cast immobilization due to the growth potential of the immature skeletal. But in elder age group Intramedullary K wire fixation through retrograde approach is the most invasive and less complicated procedure to ensure the prevention of deformity and restore the functions. Aim: To evaluate the effectiveness of the treatment of diaphyseal fractures of forearm in children with intramedullary K wire fixation through retrograde approach and look for short term and immediate results. Methodology: This was a prospective observational hospital based study carried out in Nepalgunj Medical College Teaching Hospital from January 2012 to December 2013, in children between 5-15 years with K wires for diaphyseal fractures of forearm through retrograde approach which was followed up for 12 months. All patients underwent close reduction and intramedullary K wire fixation retrograde. At 6, 12 and 48 weeks; range of motion and tenderness were looked for. Results: There were 32 patients in the study with average age of 10.41 years for male and 10.21 years for female. Average time for union was 7.3 weeks. There were no nonunion and malunions in follow ups. At 6 months all had full range of motion without any complications. Conclusion: Operative treatment with K wires through retrograde approach for diaphyseal fractures of forearm is an invasive procedure for less complications, patient’s comfort and early range of motion. JNGMC Vol. 14 No. 1 July 2016, Page: 27-31